Optimization of Manufacturing liquid Soap Based on Virgin Coconut Oil with a Combination Potassium Hydroxide and Ammonium Hydroxide - Kurniawati, Yesi; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2022)
Virgin coconut oil has a better saponification effect than coconut oil in general. It has a high lauric acid content of 46%, suitable for skin moisture; it is good to be used as a primary ingredient for making natural liquid soap; hydrolysis is carried out on VCO to get free fatty acids ingredient raw material for making soap. This study will use a combination of KOH and NH4OH bases to produce more soluble soap in water. This study aims to determine the quality of natural liquid soap from the saponification process between VCO hydrolysis and base, whether by applicable quality standards, and determine the effect of base concentration, time, and temperature of mixing on the quality of the soap produced. The method in this study uses the Response Surface Methodology, where the resulting soap product is tested for physicochemical tests. The critical value for optimizing liquid soap is obtained at the KOH base ratio of 8, time 140 minutes, and temperature 92oC, and the critical value of FFA is 0, 21%. The best soap results are sample 6, which complied with SNI 06-4085-1996 and SNI 3532-2016.